Comparative Analysis of Class Action Settlements: Key Factors in the Australian and Indonesian Legal Frameworks - Tulaseket, Revivo; Alshahrani, Ali (Tumou Tou Law Review, 2024)
This essay explores the differences in settlement outcomes for class action cases between Australia and Indonesia. It examines the reasons behind the higher prevalence of settlements in Australia compared to the relatively low number of settled cases in Indonesia. The analysis considers factors such as variations in legal systems, judicial approaches, and economic considerations that contribute to this disparity. Through a comparative analysis methodology, the essay examines legislative provisions, case law, and academic literature in both jurisdictions. The findings highlight Australia's well-established legal framework for settlements, active judicial involvement, third-party assistance, and the consideration of adversarial costs as factors that favor settlement outcomes. In contrast, the limited scope of class action proceedings in Indonesia, frequent case dismissals, complex settlement processes, and higher plaintiff costs hinder the settlement option. This study sheds light on the implications of these factors on class action settlements in Australia and Indonesia. Keywords: Class actions; Settlement Outcomes; Comparative Analysis